In-situ generated TiB2 reinforced GH3230 high-temperature alloy and preparation method thereof

By generating the TiB2 enhanced phase in situ in GH3230 high-temperature alloy, the problem of high uniform distribution of thermal cracking and enhanced phases in laser powder bed processing is solved, and the mechanical properties and cost reduction of the alloy are improved.

CN119194168APending Publication Date: 2024-12-27NINGBO ZHONGKE XIANGLONG LIGHTWEIGHT TECH CO LTD

Patent Information

Application Number
CN202411293659.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the melt processing of laser powder bed, GH3230 high-temperature alloy has thermal cracking due to large solidification temperature range and low melting point element enrichment. The existing uniform distribution method of enhanced phase is costly, which affects the mechanical properties of the materials.

Method used

By mechanically mixing titanium powder and Fe2B powder with GH3230 powder, and using selective laser melting forming technology to generate TiB2 enhanced phase in situ during the forming process, uniform distribution and strengthening of TiB2 are achieved.

Benefits of technology

It reduces economic and time costs, improves the tensile strength, yield strength and elongation of the alloy, ensures the nano-level distribution and uniformity of TiB2 particles, and avoids thermal cracking problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194168A_ABST
    Figure CN119194168A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ generated TiB2 reinforced GH3230 high-temperature alloy and a preparation method of the in-situ generated TiB2 reinforced GH3230 high-temperature alloy. The in-situ generated TiB2 reinforced GH3230 high-temperature alloy comprises a GH3230 high-temperature alloy component and a TiB2 component, the content of the TiB2 component is 0.3 to 1.5 weight percent; the TiB2 reinforced GH3230 high-temperature alloy is prepared by mechanically and uniformly mixing GH3230 high-temperature alloy powder, titanium powder and Fe2B powder and carrying out selective laser melting forming technology. The TiB2 component is generated in situ in the selective laser melting forming process. The TiB2 enhanced GH3230 high-temperature alloy is prepared through selective laser melting forming, and TiB2 is generated in situ in the forming process; the method is easy to operate, high in practicability and suitable for industrial production, the economic cost and the time cost can be reduced, and the tensile strength, the yield strength and the ductility of the alloy material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-temperature alloys, and in particular to an in-situ generated TiB2 reinforced GH3230 high-temperature alloy and a preparation method thereof. Background Art

[0002] GH3230 alloy is a solid solution strengthened Ni-Cr-W-Mo high temperature alloy. The alloy has good high temperature thermal strength and thermal stability at 1000℃ and is widely used in hot end components of aircraft engines. However, laser powder bed melting is a non-equilibrium solidification process. The molten pool undergoes 10 3 -10 7 Ultra-fast melting and repeated rapid temperature rise / fall thermal cycles at the K / s level introduce uneven residual thermal stresses into the material. For GH3230 alloy, there is a large solidification temperature range during the solidification process, and low-melting-point elements such as Cr, B, C, and Si are enriched in the last solidification area, resulting in a large range of mushy areas. Thermal cracking is very likely to occur under the action of residual tensile stress, which seriously affects the mechanical properties of the material.

[0003] In order to solve the problem of cracking in GH3230 additive manufacturing, the invention patent application with publication number CN113061782A proposed a method of adding TiB 2 Method for eliminating micro cracks in GH3230 selective laser melting, nano-TiB 2 The particles are added by mechanical mixing, but due to the ceramic phase TiB 2 Poor wettability with GH3230 substrate and TiB 2 Uneven mixing and agglomeration in GH3230 alloy powder, growth of reinforcement phase particles after SLM forming and post-processing will eventually affect the quality of the formed parts.

[0004] In addition to mechanical mixing to add reinforcement phases, the in-situ addition method of pre-alloying powder preparation has also been widely mentioned. Although this method can achieve uniform distribution of reinforcement phases, it requires high economic and time costs. Therefore, there is an urgent need for a convenient and feasible in-situ generation method of reinforcement phases for selective laser melting to prepare GH3230 high-temperature alloys. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide an in-situ generated TiB2 reinforced GH3230 high temperature alloy and a preparation method thereof. 2 B powder and GH3230 powder were prepared by mechanical mixing, and TiB was prepared by selective laser melting. 2 Reinforced GH3230 high temperature alloy, TiB 2The invention is simple to operate, highly practical, and suitable for industrial production. It can not only reduce economic and time costs, but also improve the tensile strength, yield strength, and elongation of alloy materials.

[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0007] An in-situ generated TiB 2 Strengthened GH3230 high temperature alloy, including GH3230 high temperature alloy components and TiB 2 Component; the TiB 2 The content of the component is 0.3-1.5wt%; the TiB 2 Strengthening GH3230 high temperature alloy is to combine GH3230 high temperature alloy powder, titanium powder, Fe 2 B powder is mechanically mixed and uniformly prepared by selective laser melting forming technology; the TiB 2 The components are generated in situ during the selective laser melting process.

[0008] Furthermore, the GH3230 high-temperature alloy components include, by weight percentage, Cr 20.0-24.0%, W13-15%, Mo 1-3%, Mn 0.3-1%, Si 0.25-0.75%, Al 0.2-0.5%, La 0.005-0.05%, C 0.05-0.15%, Co 0-5%, Fe 0.2-2%, Cu 0-0.5%, Ti0-0.1%, P 0-0.03%, S 0-0.015%, B 0-0.015%, and the balance is Ni.

[0009] Furthermore, the particle size of the GH3230 alloy powder is 15-53 μm.

[0010] Furthermore, the particle size of titanium powder is 0.5-5 μm, Fe 2 The particle size of B powder is 0.5-5 μm.

[0011] The present invention also provides a method for in-situ generating TiB 2 The preparation method of the reinforced GH3230 high temperature alloy is as follows: GH3230 high temperature alloy powder is mixed with titanium powder, Fe 2 The B powder is mechanically mixed and uniformly formed into a ceramic phase TiB by selective laser melting. 2 Strengthening GH3230 high temperature alloy; TiB 2 The components are generated in situ.

[0012] Furthermore, the process parameters of the selective laser melting forming method are: laser power 150-350W, scanning speed 700-1200mm / s, scanning spacing 0.07-0.11mm, and powder layer thickness 0.03-0.06mm.

[0013] More specifically, the preparation method comprises the following steps:

[0014] GH3230 high temperature alloy powder and titanium powder, Fe 2 The B powder is mechanically mixed evenly, and then the mixed powder is placed in a vacuum drying oven for drying at a temperature of 80-150°C for 4-8 hours;

[0015] The dried mixed powder is placed in the SLM equipment, 316L or 304L stainless steel is selected as the substrate, the substrate is preheated at 80-200°C, argon gas is introduced, the oxygen content is controlled below 100ppm, and selective laser melting is performed.

[0016] Furthermore, mechanical mixing is performed using a V-type powder mixer with a rotation speed of 15-30 r / min and a mixing time of 4-10 h.

[0017] Furthermore, in the mixed powder, the addition amount of Ti is 0.2-1wt%, Fe 2 The addition amount of B is 1-4 wt%.

[0018] Furthermore, after the selective laser melting forming, the obtained formed sample is subjected to a solution treatment, and the solution treatment process conditions are: heating rate 2-10°C / min, target temperature range: 1000-1250°C, holding time range: 1-4h, cooling method: air cooling or argon quenching.

[0019] The beneficial effects of the present invention are:

[0020] (1) The present invention utilizes “in-situ reaction” to generate nano-scale TiB during laser additive manufacturing 2 Ceramic particles strengthen the TiB 2 The ceramic particles are evenly distributed in the GH3230 alloy matrix;

[0021] Specifically, Fe 2 B powder, Ti powder, and GH3230 powder are mixed. During the laser additive manufacturing process, the powder melts into a liquid state and TiB can be generated in situ. 2 , the grain boundary energy is low, so TiB 2 The particles will be dispersed to the grain boundaries; because there will be "countless" molten pools in the additive manufacturing process, these molten pools will "spatially" separate TiB 2After the alloy solidifies, there are a lot of grains inside the molten pool. These grains once again "space" TiB 2 Distributed, so TiB 2 The particles are evenly distributed in the alloy matrix;

[0022] In addition, due to the ultra-high cooling rate of laser additive manufacturing, it is ~10 6 K / s, in-situ generation of TiB 2 It can solidify in a short time without further coarsening and growth, so TiB 2 The particle size is at the nanometer level, which can effectively increase the nucleation rate on the one hand, and effectively pin the grain boundaries on the other hand, thereby refining the grains.

[0023] (2) The titanium powder and Fe 2 B powders are all micron-sized powders, and Fe 2 B powder has a lower melting point and is more likely to undergo chemical reactions during the selective laser melting process than pure boron powder, ensuring that the in-situ reaction proceeds smoothly and generates the target product, thus playing a role in strengthening the matrix.

[0024] (3) The present invention combines titanium powder, Fe 2 B powder and GH3230 powder are mixed evenly by mechanical mixing method, and TiB is generated in situ during the selective laser melting process. 2 Compared with pre-alloying powder preparation, this method reduces economic and time costs, is simple to operate, and has strong practicality;

[0025] (4) Compared with directly converting TiB 2 The method of mechanically mixing the powder with GH3230 powder, the TiB prepared by the present invention 2 The elongation of the reinforced GH3230 high-temperature alloy has increased by more than 1.5 times, and the tensile and yield strengths exceed the industry standard requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the powders of Example 1 after being uniformly mixed;

[0027] Figure 2 This is a metallographic picture of the alloy after solution treatment in Example 2;

[0028] Figure 3 This is a metallographic picture of the alloy after solution treatment in Comparative Example 1;

[0029] Figure 4 This is the metallographic picture of the alloy after solution treatment of Comparative Example 2. DETAILED DESCRIPTION

[0030] The technical solutions in the present invention will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present invention provides a method for in-situ generating TiB 2 Strengthened GH3230 high temperature alloy, which includes GH3230 high temperature alloy component and TiB 2 Component; the TiB 2 The content of the component is 0.3-1.5wt%; the TiB 2 Strengthening GH3230 high temperature alloy is to combine GH3230 high temperature alloy powder, titanium powder, Fe 2 B powder is mechanically mixed and uniformly prepared by selective laser melting forming technology; the TiB 2 The components are generated in situ during the selective laser melting process.

[0032] The GH3230 high temperature alloy components include, by weight percentage, Cr 20.0-24.0%, W 13-15%, Mo 1-3%, Mn 0.3-1%, Si 0.25-0.75%, Al 0.2-0.5%, La 0.005-0.05%, C 0.05-0.15%, Co 0-5%, Fe 0.2-2%, Cu 0-0.5%, Ti 0-0.1%, P 0-0.03%, S 0-0.015%, B 0-0.015%, and the balance is Ni. The particle size of the GH3230 alloy powder is 15-53 μm.

[0033] Among them, the particle size of titanium powder is 0.5-5μm, Fe 2 The particle size of B powder is 0.5-5 μm.

[0034] The present invention also provides a method for in-situ generating TiB 2 The preparation method of reinforced GH3230 high temperature alloy is as follows: GH3230 powder is mixed with titanium powder, Fe 2 The B powder is mechanically mixed and uniformly formed into a ceramic phase TiB by selective laser melting. 2 Strengthening GH3230 high temperature alloy; TiB 2 The components are generated in situ.

[0035] Specifically, the preparation method comprises the following steps:

[0036] GH3230 powder and titanium powder, Fe 2B powder is mechanically mixed evenly; in the mixed powder, the addition amount of Ti is 0.2-1wt%, Fe 2 The addition amount of B is 1-4wt%; the mechanical mixing is carried out by using a V-type powder mixer, the speed is 15-30r / min, and the mixing time is 4-10h; then the mixed powder is placed in a vacuum drying oven for drying, the baking temperature is 80-150℃, and the time is 4-8h;

[0037] Put the dried mixed powder into the SLM equipment, select 316L or 304L stainless steel as the substrate, preheat the substrate, and the preheating temperature is 80-200℃; before printing, modeling and slicing are performed; during the forming process, argon gas is introduced to control the oxygen content below 100ppm, and selective laser melting is performed. The process parameters of the selective laser melting forming method are: laser power 150-350W, scanning speed 700-1200mm / s, scanning spacing 0.07-0.11mm, powder layer thickness 0.03-0.06mm; the scanning strategy is 67° strip scanning;

[0038] After selective laser melting, the obtained formed samples are solution treated. The solution treatment process conditions are: heating rate 2-10℃ / min, target temperature range: 1000-1250℃, holding time range: 1-4h, cooling method: air cooling or argon quenching.

[0039] The present invention is further described in detail below through specific examples.

[0040] Example 1

[0041] raw material:

[0042] GH3230 alloy powder, comprising the following components by weight percentage: Cr 22.0%, W 15%, Mo1%, Mn 0.8%, Si 0.55%, Al 0.35%, La 0.01%, C 0.08%, Co 1%, Fe 0.8%, Cu 0.05%, Ti 0.05%, P 0.01%, S 0.001%, B 0.005%, and the balance is Ni; wherein the average particle size of the GH3230 alloy powder is 30 μm;

[0043] The addition amount of Ti powder is 0.27wt%, Fe 2 The addition amount of B powder is 1.45wt%.

[0044] In situ generation of TiB 2 The preparation method of the reinforced GH3230 high temperature alloy comprises the following steps:

[0045] S1, titanium powder, Fe 2B powder and GH3230 powder were mixed in a V-type powder mixer at a speed of 25r / min for 8h; then the mixed powder was placed in a vacuum drying oven for drying at a temperature of 120℃ for 6h; Figure 1 1 is a SEM image of the powder after uniform mixing of Example 1, (a) and (b) respectively represent SEM images at two different magnifications; Figure 1 As shown, after mixing, Fe 2 B and Ti powders adhere to the surface of GH3230 spherical particles without a large amount of agglomeration.

[0046] S2, put the dried mixed powder into the SLM equipment, select 316L stainless steel as the substrate, and preheat the substrate at a preheating temperature of 130°C;

[0047] S3, modeling and slicing before printing;

[0048] S4, introduce argon gas, control the oxygen content below 100ppm, and perform selective laser melting. The scanning strategy used for printing is 67° strip scanning; the process parameters of the selective laser melting method are: laser power 260W, scanning speed 1000mm / s, scanning spacing 0.08mm, powder layer thickness 0.05mm;

[0049] S5, after printing is completed, the sample is subjected to solution treatment, the system is: heating to 1150℃ at 10℃ / min, keeping warm for 1h, and air cooling.

[0050] The TiB of Example 1 2 In-situ generated TiB in reinforced GH3230 superalloy 2 The content is 0.4wt%; after solution treatment, the tensile strength, yield strength and elongation of the alloy are 840MPa, 476MPa and 28.6% respectively.

[0051] Example 2

[0052] Compared with Example 1, the amount of raw material added has changed. Specifically, the amount of Ti added is 0.48wt%, Fe 2 The addition amount of B is 2.46wt%; TiB 2 In-situ generated TiB in reinforced GH3230 superalloy 2 The content is 0.7wt%.

[0053] like Figure 2 The metallographic results show that no obvious microcrack defects were found in the samples after heat treatment.

[0054] The tensile strength, yield strength and elongation of the alloy after solution treatment in Example 2 are 903 MPa, 515 MPa and 23.8%, respectively.

[0055] Example 3

[0056] Compared with Example 1, the amount of raw material added has changed. Specifically, the amount of Ti added is 0.7wt%, Fe 2 The addition amount of B is 3.5wt%; TiB 2 In-situ generated TiB in reinforced GH3230 superalloy 2 The content is 1wt%.

[0057] The tensile strength, yield strength and elongation of the alloy after solution treatment in Example 3 are 930 MPa, 550 MPa and 18.7%, respectively.

[0058] Comparative Example 1

[0059] Compared with Example 2, the amount of raw material added has changed; specifically, the amount of Ti added is 1.4wt%, Fe 2 The addition amount of B is 7wt%; the in-situ generated TiB 2 The content is 2wt%.

[0060] Ti and Fe 2 The increase in B content leads to agglomeration of powders during mixing; Figure 3 The metallographic results show that a large number of microcracks are formed along the printing direction of the sample after heat treatment.

[0061] The tensile strength, yield strength and elongation of the alloy after solution treatment in this comparative example are 786 MPa, 430 MPa and 16%, respectively.

[0062] Comparative Example 2

[0063] Compared with Example 3, the difference is that the raw material addition method is changed, that is, commercially available irregular 1wt% TiB 2 (particle size range is between 0.5-5 μm) and GH3230 powder are mechanically mixed, and the mixing method is consistent with Example 3.

[0064] Results: Agglomeration occurred during powder mixing; e.g. Figure 4 The metallographic results show that after heat treatment, the sample has obvious microcracks along the printing direction. The mechanical properties are significantly reduced compared with Example 3. The tensile strength, yield strength and elongation of the alloy after solution treatment in this comparative example are 790MPa, 360MPa and 14.3%, respectively.

[0065] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0066] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An in-situ generated TiB2 reinforced GH3230 high temperature alloy, characterized in that: It comprises a GH3230 high temperature alloy component and a TiB2 component; the content of the TiB2 component is 0.3-1.5wt%; the TiB2 enhanced GH3230 high temperature alloy is prepared by mechanically mixing GH3230 high temperature alloy powder, titanium powder and Fe2B powder uniformly and then using a selective laser melting forming technology; the TiB2 component is generated in situ during the selective laser melting forming process.

2. The in-situ generated TiB2 reinforced GH3230 high temperature alloy according to claim 1, characterized in that: The GH3230 high-temperature alloy components include, by weight percentage, Cr 20.0-24.0%, W13-15%, Mo 1-3%, Mn 0.3-1%, Si 0.25-0.75%, Al 0.2-0.5%, La 0.005-0.05%, C 0.05-0.15%, Co 0-5%, Fe 0.2-2%, Cu 0-0.5%, Ti 0-0.1%, P 0-0.03%, S 0-0.015%, B 0-0.015%, and the balance is Ni.

3. The in-situ generated TiB2 reinforced GH3230 high temperature alloy according to claim 1, characterized in that: The particle size of GH3230 alloy powder is 15-53 μm.

4. The in-situ generated TiB2 reinforced GH3230 high temperature alloy according to claim 1, characterized in that: The particle size of the titanium powder is 0.5-5 μm, and the particle size of the Fe2B powder is 0.5-5 μm.

5. A method for preparing an in-situ generated TiB2-enhanced GH3230 high temperature alloy, characterized in that: GH3230 high temperature alloy powder is mechanically mixed with titanium powder and Fe2B powder, and a ceramic phase TiB2 reinforced GH3230 high temperature alloy is prepared by a selective laser melting forming method; during the selective laser melting forming process, the TiB2 component is generated in situ.

6. The method for preparing the in-situ generated TiB2 reinforced GH3230 high temperature alloy according to claim 1, characterized in that: The process parameters of the selective laser melting forming method are: laser power 150-350W, scanning speed 700-1200mm / s, scanning spacing 0.07-0.11mm, and powder layer thickness 0.03-0.06mm.

7. The method for preparing the in-situ generated TiB2 reinforced GH3230 high temperature alloy according to claim 1, characterized in that: The steps include: GH3230 high temperature alloy powder, titanium powder and Fe2B powder are mechanically mixed evenly, and then the mixed powder is placed in a vacuum drying oven for drying at a temperature of 80-150°C for 4-8 hours; The dried mixed powder is placed in the SLM equipment, 316L or 304L stainless steel is selected as the substrate, the substrate is preheated at 80-200°C, argon gas is introduced, the oxygen content is controlled below 100ppm, and selective laser melting is performed.

8. The method for preparing the in-situ generated TiB2 reinforced GH3230 high temperature alloy according to claim 5 or 7, characterized in that: Mechanical mixing uses a V-type powder mixer with a rotation speed of 15-30r / min and a mixing time of 4-10h.

9. The method for preparing the in-situ generated TiB2 reinforced GH3230 high temperature alloy according to claim 5 or 7, characterized in that: In the mixed powder, the added amount of Ti is 0.2-1wt%, and the added amount of Fe2B is 1-4wt%.

10. The method for preparing the in-situ generated TiB2 reinforced GH3230 high temperature alloy according to claim 5 or 7, characterized in that: After selective laser melting, the obtained formed samples are solution treated. The solution treatment process conditions are: heating rate 2-10℃ / min, target temperature range: 1000-1250℃, holding time range: 1-4h, cooling method: air cooling or argon quenching.

Citation Information

Patent Citations

  • GH3230 nickel-based high-temperature alloy material, method for eliminating selective laser melting forming microcracks and application of GH3230 nickel-based high-temperature alloy material

    CN113061782A

Cited By

  • Heat-resistant high-strength CoCrNi-based medium-entropy alloy based on cellular dislocation structure regulation and preparation method thereof

    CN120920744A